Dopamine Transporter Scan: Determining the Diagnostic Performance of Hermes Brain Registration and Analysis Software Suite with Parkinson Disease and Essential Tremor Disease Patients - Bamaalabong, Peter Paul; Sarfo-Antwi, Frederick; Danaah Malick, Martin Mumuni (International Journal of Innovative Research in Medical Science, 2021)
Parkinson Disease is the most baffling and complex of all neurological disorders because its causes barely remain a mystery. The hallmark of Parkinson Disease (PD) is the loss of brain cells that transport dopamine in the basal ganglia of the brain. The study devised a robust semi-quantitative brain analysis technique to accurately differentiate patients with PD from patients with Essential Tremor (ET). The mode of data collection was retrospective since the brain scans, consisting PD and ET patients, were previously carried out using a Toshiba SPECT scanner. The sample size was made up of 15 brain scans of ET and PD patients. Five Hermes BRASS techniques were used to determine the specific bindings and binding ratios in the putamen and caudate regions of the brain while the mean binding ratios were calculated using MS Excel. Hermes BRASS techniques numbers; 2, 3 and 4 (Table 8) misdiagnosed one patient out of the 15 patients. However, notable was the fact that diagnostic technique number 3 had no instance of coincidence diagnosis. The graphical and numerical outcomes obtained with Hermes BRASS and MS Excel showed that a population of PD patients was separable from a population of ET disease patients. T-test confirmed that value of the derived t-statistics (0.19) was less than value of the t-statistics (2.18). Hence the alternate hypothesis was accepted since the difference between the two populations was significant. The quest to identify a robust Hermes diagnostic technique that differentiates patients with PD from patients with ET was successfully realized where the Hermes New BRASS had remarkable improvement over the Hermes Old BRASS. Most essentially the incidence of misdiagnosis, in the differentiation of patients with PD from patients with ET, was minimized to one patient out of the 15 patients. This translated to patients deriving maximum benefit from the pool of medical drugs available for the treatment of PD and ET patients.